An Analysis of Education Reforms and Assessment in the Core Subjects Using an Adapted Maslow's Hierarchy: Pre and Post COVID-19 - Jennifer Ansorger (MDPI AG, 2021)
Through the lens of an adapted Maslow's hierarchy of needs, I have analyzed (1) the impact of the three main educational reforms of the 20th and 21st centuries on culturally and linguistically diverse (CLD)and low-socioeconomic (SES)students in the core subjects up to the COVID-19 pandemic; (2) the efficacy of current classroom assessment practices, and (3) a brief reimagining of how changing equity standards in teaching and assessment post-COVID-19 could aid in CLD and low-SES students achieving a higher self-esteem level. I contend that student success, or self-esteem, can only be achieved by first satisfying the needs at the lower hierarchy levels. By analyzing CLD and SES students' school experiences, educators and policy-makers can extrapolate the requirements for inclusive, rigorous, and responsive assessments that recognize students' needs and utilize their cultural and linguistic diversity. As states begin the shift from remote learning back to face-to-face in the fall, more significant considerations of CLD and low-SES students must be ensured.